Programa de estimulación para fortalecer la velocidad de procesamiento de información en la toma de decisiones en futbolistas (2021)
Recently it has been suggested that success in soccer depends on how information is processed given the context, given that the individual result is of select interest in the discrepancy of decision making and the activation of cognitive processes to unify a number of actions in a unit of time. Likewise, it implies analyzing the relation of desertion and difficulty in young soccer players from Tolima to solidly reach the jump of professional quality, where there is an axis problem of the absence of young athletes in Colombian soccer and at world level. Objective: To determine the effect of a stimulation program to improve the speed of information processing and decision making in soccer players from the city of Ibagué. Methodology: The population is made up of 9 adolescents, aged between 16 and 20 years old, in the youth category of the Academia Tolimense Sports Club. This research is carried out under the method of the empirical-analytical paradigm,